Design, Implementation, and Evaluation of an Electronic Course of Sexual Health Education for Young Adults (18–35 Years): An Exploratory Sequential Mixed‐Methods Study Protocol - Sanam Borji‐Navan; Shahrbanoo Salehin; Tahereh Naseri‐BooriAbadi; Shahrbanoo Goli; Mojgan Mirghafourvand (Health Science Reports, 2025)
ABSTRACT Background and Aims Sexual health education is crucial for young adults well‐being, yet effective interventions are lacking in Iran. E‐learning offers a promising avenue to deliver comprehensive sexual health education, tailored to the cultural context and diverse needs of Iranian young adults. This mixed‐methods study with an exploratory sequential design aims to design, implement, and evaluate an electronic sexual health education course for Iranian young adults (18–35 years). The study has two phases: 1. needs assessment and course design, and 2. course implementation and evaluation. Methods and Analysis Phase one involves a systematic review of e‐learning interventions and national/international guidelines, followed by qualitative research to explore young adults and key informants' perspectives on sexual health educational needs. These findings will inform the design and development of the e‐course. Phase two will be a randomized controlled trial (RCT) involving nonmedical science students at Guilan University. The intervention group will receive the e‐course, while the control group will not. Outcomes will be assessed using validated questionnaires, focusing on sexual health. Ethics and Dissemination This protocol has been approved by the Ethics Committee of the Shahroud University of Medical Sciences, Semnan, Iran (code number: IR.SHMU.REC.1403.085). All the steps/methods will be performed in accordance with the relevant guidelines and regulations. Ethical Code IR.SHMU.REC.1403.085. URL: https://ethics.research.ac.ir/EthicsProposalView.php?id=494573. PROSPERO Registration Number CRD42024573968, CRD42024578450. Trial Registration Iranian Registry of Clinical Trials (IRCT): IRCT20210313050689N1. URL: https://irct.behdasht.gov.ir/trial/79322.